Accumulation rates and sources of sediments and organic carbon on the Palos Verdes shelf based on multiple radioisotopic tracers (137Cs, 239,240Pu, 210Pb, 234Th, 238U and 14C) - Santschi, P. H.; Guo, L.; Asbill, S.; Allison, M.; Kepple, B.; Wen, L. S. (Marine Chemistry, 2001)
We report here bioturbation and sediment accumulation rates determined from replicate sediment cores at four different sampling sites on the Palos Verdes shelf, Southern California, using bomb fallout and natural radionuclides (137Cs, 239,240Pu, 210Pb, 234Th, and 14C), along with supporting measurements of organic carbon (OC), porosity and granulometry. Present-day particle reworking, on time scales of several months, is restricted to the upper 3 cm, with rates ranging from 13 to 200 cm2/year, as deduced from 234Thxs profiles. There is little evidence that particle reworking reached depths significantly greater than 5 cm. Post-1963 (or post-1971) sediment accumulation rates ranged from 0.7 to 1.4 g/cm2/year (equivalent to 1.1–1.8 cm/year for surficial sediments), as calculated from Pu and Cs isotope profiles, with little change over time or distance from the outfall. Lateral transport of older sediment and multiple sediment sources on the Palos Verdes shelf is suggested from radiocarbon measurements on foraminifera and bulk sedimentary organic matter at two sampling sites, which showed variable, old and refractory sources of OC. Pre-1953 sediments accumulated at rates that were at least 0.4 g/cm2/year (≥0.3 cm/year), based on 210Pbxs dating. Given the abundance of sediment sources to the Palos Verdes shelf, the high sedimentation rates, and shallow particle mixed layers, contaminant-enriched layers should continue to move deeper into the sediments.
id: 1309